Edukasi dan Deteksi Dini Kesehatan Telinga pada Populasi Lanjut Usia St. Anna - Sari, Triyana; Firmansyah, Yohanes; Sugiharto, Hans; Averina, Friliesa; Satyanegara, William Gilbert; Kurniawan, Joshua (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2024)
Aging causes degenerative changes in the auditory system, making ear health an important aspect of geriatric care. Hearing loss is common in elderly and impacts in their quality of life, mental health and cognitive function. Self-cleaning of the ears, involves inserting objects into the ear canal, poses significant risks including earwax accumulation and eardrum injury. This causes conditions such as otitis externa and tympanic membrane perforation. This activity uses the PDCA (Plan-Do-Check-Act) methodology, which aims for physical examination and ear health education. This activity involved 38 participants, 12 men and 26 women. Physical examination revealed 2 participants (5.3%) with right and left eardrum perforations, 9 participants (23.7%) with prop cerumen in the right ear, and 8 participants (21.1%) in the left ear. Implementing proper ear care practices and regular physical ear examinations, elderly can improve their hearing health and quality of life.